Home Gardening Food Safety: Washing the Fruits (and Vegetables) of Your Labor Properly - Eshani Persaud; Amy Simonne; Karla P. Shelnutt (EDIS)
Having a home garden has become popular recently. It is a great way to enjoy fresh fruits and vegetables—foods that are an important part of a healthy diet. However, just because you have your own garden and control how it is treated does not make the fruits and vegetables you grow safer than those you buy in the store. To reduce the chance of getting sick from foodborne illnesses, you must wash the fruits and vegetables you grow before eating them raw or cooked. This publication helps you learn the proper way to clean your fruits and vegetables so you can enjoy them safely. This 4-page fact sheet was written by Eshani Persaud, Amy Simonne, and Karla P. Shelnutt, and published by the UF Department of Family Youth and Community Sciences, November 2013. http://edis.ifas.ufl.edu/fy1401